Ending Covid-19 Vaccine Apartheid through Vaccine Donations: The Influence of Supply Chains - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study determinants of COVID-19 vaccine donations from recipients' perspective, especially considering supply chain and institutional weakness (corruption) aspects. Results, based on data from more than 131 nations, show that strengthened supply chains reduced donations. The impacts of corruption and logistics performance likely persisted from pre-COVID times. More corrupt nations received fewer donations per capita, ceteris paribus. The results with respect to economic prosperity supported efforts to end vaccine apartheid, and island nations received more donations, as did nations with more bilateral vaccine deals. Finally, donations received through COVAX were driven by qualitatively similar factors, except corruption did not matter.
Keywords: L90; K42; I18; 330; Covid-19; vaccine donations; equity; supply chain; corruption; logistics; international shipments; pandemic; government COVAX